Investigating the Bilingual Education Program at Malhikdua School - Mohammad Umar Fakhrudin; Nugraha, Pramudya Wisnu; Putri, Novita; Nurfitriyani, Vivi (EDUPEDIA Publisher, 2024)
This research delves into the curriculum design and evolution of the bilingual program at MA Al Hikmah 2, popularly known as Malhikdua School. Employing qualitative methodologies, data were gathered through direct observations and interviews. The program’s innovations include four English proficiency programs: School Outing Program, Test of English as Foreign Language, English Competency Test by LPKS, and Malhikdua Explore. The findings demonstrate the effectiveness of the Malhikdua bilingual program in advancing students’ English proficiency through a strategically designed and supportive English proficiency programs.